Antimicrobial polymers: Antibacterial efficacy of silicone rubber–titanium dioxide composites. (July 2017) - Felice, Betiana; Seitz, Vera; Bach, Maximilian; Rapp, Christin; Wintermantel, Erich
Control and reduction of microorganism infections in high-risk environments is up to date a challenge. Traditional techniques imply several limitations including development of antibiotics resistance and ecotoxicity. Then, polymers functionalized with photocatalyts arise as a promising solution against a broad spectrum of microorganisms found at, e.g. sanitary, food, and medical environments. Here, we present silicone rubber–TiO2 composites as novel antibacterial polymers. Four different types of composites with different TiO2 contents were produced and analyzed under UV irradiation and dark conditions in terms of particle distribution, chemical composition, photocatalytic activity, wettability, and antibacterial efficacy against Escherichia coli . Under UV irradiation, antibacterial sensitivity assay showed a 1000 times reduction of colony forming units after 2 h of light exposure so that the antibacterial ability of silicone–TiO2 composites was proved. Photocatalytic activity assessment suggested that reactive oxygen species induced by photocatalytic reaction at TiO2 particles are the main cause of the observed antibacterial effect. Scanning electron microscopy indicated no topographical damage after UV exposure. In addition, chemical analysis through Raman and X-Ray photoelectron spectroscopies demonstrated the stability of the silicone matrix under UV irradiation. Hence, the current work presents silicone–TiO2 composites as stable nonspecific antibacterial polymers for prevention of infections at multiple high-risk environments.